2021
DOI: 10.1177/10848223211000048
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Effect of Education Based on the Theory of Planned Behavior on the Mothers’ Preventive Practices Regarding Toddler Home Injuries

Abstract: Home injuries are among the causes of death and disability in toddlers. Preventing home injuries is an essential part of the child health care program. Using education-based models interventions can promote mothers’ practices regarding home injuries. This study aimed to investigate the effect of education based on the theory of planned behavior (TPB) on the mothers’ preventive practices regarding toddler home injuries. A quasi-experimental study was conducted on 116 mothers referred to comprehensive health cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 37 publications
(41 reference statements)
0
3
0
Order By: Relevance
“…In this study, the patients considered researchers, doctors, and nurses as the most significant cues to action. However, in other studies, TV, parents, teachers, and health coaching were the most important cues to action (24,36,37).…”
Section: Discussionmentioning
confidence: 89%
“…In this study, the patients considered researchers, doctors, and nurses as the most significant cues to action. However, in other studies, TV, parents, teachers, and health coaching were the most important cues to action (24,36,37).…”
Section: Discussionmentioning
confidence: 89%
“…The high frequency of depressed mood in students at the beginning of their studies at Hamadan University of Medical Sciences can be related to factors such as participating in a difficult university entrance exam, tough competition for university admission, tolerating family pressure to pass the university entrance exam, and having concerns about their future jobs and even failure in admission to their favorite universities and fields of study. However, further studies are needed to determine the exact factors in this respect (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Regarding the effect of demographic characteristics on mental disorders, the results of this study showed that the students' higher educational degree, Shahed and Isargar admission quota, low financial status, and father's unemployment increase the chance of developing mental disorders in the participants.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, attitudes integrate visions, perspectives, and ways of thinking about aspects of child´s upbringing or development, the roles and responsibilities of parents (National Academies of Sciences, Engineering, and Medicine et al, 2016). This is related to childcare practices according to authors such as Hamilton, van Dongen & Hagger (2020) and Amini et al (2021), who contemplate the relationship of attitudes, subjective norms, and planned behavior in the prevention practices adopted by caregivers. Thus, care practices are defined as actions carried out by primary caregivers to provide food, health care, physical and cognitive stimulation, and emotional support that guarantee the well-being of the child and the satisfaction of their physical and emotional needs (Pino et al, 2017;Lenta et al, 2020;Dos Santos et al, 2023).…”
Section: Introductionmentioning
confidence: 99%